Risky mortgages, credit shocks and cross-border spillovers - Alejandro Buesa; Alicia de Quinto; Javier Población García (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper describes a novel methodology of measuring risky and conservative mortgage credit using household survey data for 18 European Union countries and the United Kingdom. In addition, we construct time series for both types of credit and embed them into a global vector autoregressive (GVAR) model, so as to study how shocks to both variables affect domestic output and propagate across countries through cross-border banking exposures. The results show that a decrease in risky credit can have long-lasting positive effects on GDP, both in the originating country and its most exposed peers, while a fall in conservative credit is detrimental. In some geographies, negative shocks to both types of credit reduce output, a feature linked to the lower relevance of homeownership which implies that mortgage credit plays a less prominent role in the domestic economy.
Keywords: C32; F47; G21; G51; 330; Mortgage rating; LTV limits; borrower-based measures; cross-border spillovers